Modalidades de organização de produção agropecuária e características epidemiológicas da febre aftosa nos estados de Tocantins e Goiás - Valeria de Sa Jayme (1993)
The identification of the modalities of animal production becames fundamental for the more adequate and precise approad when introducing the analyses of any health problem in a given animal population. Based on this approach, the municipalities of the states of Tocantins and Goias were analysed by means of systemic focusing, using the indicators wich reflect the ecological, economic and demographic systems. Were identified distinct forms of production, was constated that in Tocantins are the modalities starter reasing (calves), complete cycle and fattening (termination), while Goiás has unities dedicate a starter reasing (calves), complete cycle, fattening and milk'sexplorations, establishing that in all of models were identified variated and distinct kind of farm production mainly in animal production, characterized by proper forms, since family insertions until impresarial. The recogntion of these productive systems permitted, taking as a reference the footh-and- mouth disease (FMD), the configuration the different ecosystems presents in each state. In Tocantins were recognized two types, the primmary and secundary ecosystems. In the state of Goias were identified primary, secundary and paraendemic ecosystems. The categorization established has conditioned the regionalization of control strategies of FMD and possibilited the insertion of the analyses of the productive modalities and the animal's health profile in a dinamic and global context, reaffirming the teoric-methodologic referencial applied.